CHX and a Face Shield Cannot Prevent Contamination of Surgical Masks - Gund, Madline P.; Naim, Jusef; Hannig, Matthias; Halfmann, Alexander; Gärtner, Barbara; Boros, Gabor; Rupf, Stefan (Frontiers in Medicine, 2022)
Background Bacterial contamination on surgical masks puts a threat to medical staff and patients. The aim of the study was to investigate its contamination during dental treatments, wearing a face shield and performing a pre-procedural mouth rinsing with chlorhexidine (CHX). Methods In this prospective, randomized study, 306 treatments were included, 141 single-tooth (restorations) and 165 total dentition treatments (preventive or periodontal supportive ultrasonic application). A total of three groups (each: n = 102) were formed: participants rinsed for 60 s with 0.1 % CHX or with water before treatment, and, for control, a non-rinsing group was included. In view of the COVID-19 pandemic, a face shield covering the surgical mask enhanced personal protective equipment. After treatment, masks were imprinted on agar plates and incubated at 35°C for 48 h. Bacteria were classified by phenotypic characteristics, biochemical assay methods, and matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS). Colonies (CFU) were counted and mean values were compared (Kruskal–Wallis-, U test, p < 0.05). Results Chlorhexidine led to a statistically significant reduction of bacterial contamination of the surgical mask (mean: 24 CFU) in comparison with water (mean: 47 CFU) and non-rinsing (mean: 80 CFU). Furthermore, rinsing with water reduced CFU significantly in comparison with the non-rinsing group. There were no significant differences between single or total dentition treatments. Streptococcus spp., Staphylococcus spp., Micrococcus spp., and Bacillus spp. dominated, representing the oral and cutaneous flora. Conclusion A pre-procedural mouth rinse is useful to reduce the bacterial load of the surgical mask. However, contamination cannot be prevented completely, even by applying a face shield. In particular, during pandemic, it is important to consider that these additional protective measures are not able to completely avoid the transmission of pathogens bearing aerosols to the facial region. If antiseptic rinsing solutions are not available, rinsing with water is also useful.